Queering chapter books with LGBT characters for young readers: recognizing and complicating representations of homonormativity. Issue 6 (1st November 2016) - Hermann-Wilmarth, Jill M.; Ryan, Caitlin L.
ABSTRACT: In this paper, we consider the limited chapter book options with lesbian, gay, bisexual, and transgender (LGBT) characters available for upper elementary readers. While these texts all include one or more LGBT character(s), the overall representations of LGBT people and issues highlight particular normative identities and silence others. We are concerned that these representations reify neoliberal ideas about sexuality's relationship to race and class, and encourage gay assimilation into normative but problematic, nonequitable institutions. Yet we also believe that an analysis of books focusing only on representations of LGBT characters' identities limits the queer potential of texts. Therefore, in addition to looking at representations within these books, we also consider how a second look at these books through a queer lens can help disrupt normative representations of a range of identity categories. We undertake this dual analysis for several purposes: (1) to find and review LGBT-inclusive chapter books available for pre-YA (young adult) readers, (2) to analyze gaps in this corpus of literature so as to push back against normativizing frameworks, and (3) to show how bringing queer critique and analysis of such texts can be used to deconstruct and diversify representations of LGBT people and families until/in addition to the publication of additional and more diverse texts.